022 A video on the implantable cardioverter-defibrillator: which counselling for the patients. (23rd September 2015) - Barnel, C; Chevalier, P
Abstract : Background and Objectives: The implantable cardioverter-defibrillator (ICD) has proven its effectiveness in preventing sudden cardiac death from arrhythmia. It improves patients' quality of life considerably from a medical point of view but many studies have shown that it is also a cause of anxiety and depression. Since patient management starts by providing information before an intervention, our cardiac rhythmology department produced an information video that would provide standardised information on ICDs, understandable by all, with the aim of reducing the preoperative anxiety level. However, standardised information is not suited to all patients; information needs to be tailored. For this reason, we studied the need for providing individual personal support with the video. Programme: The video was shown to patients, with or without their family, before admission to hospital for primary ICD implantation. The video was followed by an interview exploring the patients' and their family's views on the video and giving patients an opportunity to ask questions. An anxiety questionnaire (Spielberger's State Trait Anxiety Inventory) was administered before and after the video, and after the interview. Results: According to the results of the anxiety questionnaire, the interview had a marked effect in reducing any anxiety associated with seeing the video. This highlighted the need for counselling when an information video is shown before a medical intervention, especially when the disease engenders anxiety. Analysis of the interviews provided a valuable basis for patient counselling. Discussion and Conclusion: Preliminary counselling is needed to establish the emotional status of patients before an intervention to determine their information needs and to be able to organise individually tailored follow up. A more interactive video would help patients acquire information in a more flexible way and enable them to play a more active part in information acquisition. Contexte: D'efficacité prouvée, le défibrillateur automatique implantable (DAI) prévient la mort subite cardiaque d'origine rythmique. Du point de vue médical, cet appareil améliore considérablement la qualité de vie des patients. Toutefois, de nombreuses études soulignent qu'il est aussi un facteur d'anxiété et de dépression. Pour cette raison et parce que la prise en charge du patient commence dès l'information pré-interventionnelle, le service de rythmologie du Professeur Philippe Chevalier de l'hôpital cardiologique de Lyon a réalisé une vidéo d'information. Le but de cette vidéo était de fournir une information standardisée accessible par tous et d'agir positivement sur le niveau d'anxiété préopératoire. Or le caractère standard de l'information ne s'adapte pas à la sensibilité individuelle du patient. Pour cette raison, nous avons étudié la nécessité d'un accompagnement individualisé autour de cette vidéo. Programme: description, mise en œuvre, éléments de suivi: La vidéo d'information a été présentée aux patients accompagnés ou non de leur famille avant leur hospitalisation dans le cadre d'une primo-implantation de DAI. Le visionnage de la vidéo a été suivi d'un entretien qui consistait en l'évaluation de l'appréciation de la vidéo des patients et de leur famille suivi d'un temps d'expression libre pendant lequel, ils étaient invités à poser des questions. Un questionnaire d'anxiété (inventaire état-trait de Spielberger) a été proposé avant et après la vidéo ainsi qu'après l'entretien. Résultats en termes d'impact clinique: Les résultats de l'inventaire état-trait montrent que l'entretien a un réel effet significatif sur l'anxiété par rapport à la vidéo. Ce résultat œuvre pour l'importance de l'accompagnement dans le cadre de la présentation d'une vidéo d'information avant une intervention médicale. Ceci est d'autant plus vrai que le contexte entourant la maladie est anxiogène. L'analyse des entretiens fournis une base intéressante à l'accompagnement des patients dans ce contexte. Discussion et conclusion: Tout d'abord, un accompagnement préliminaire doit être mis en place pour déterminer le contexte émotionnel dans lequel se trouve le patient avant l'intervention afin de définir ses besoins réels en terme d'information, puis d'instaurer un suivi personnel du patient en fonction des nécessités. Pour finir, la réalisation d'une vidéo plus interactive permet une orientation individuelle de l'information, rendant le patient acteur de sa prise d'information.